Exploring the critical waste factors affecting highway construction projects in Pakistan. - Usman Aftab; Farrokh Jaleel; Mughees Aslam; Javed Ahmed Khan Tipu (PLoS ONE)
Highway construction projects are known for their propensity to consume enormous quantities of materials and their susceptibility to generate considerable waste. Adequate research has been conducted on identifying the causes of waste produced in building projects, however, there are limited studies available on identifying causative factors for highway projects. This study aims to identify and evaluate the causes and factors of waste generated on highway projects using a literature review and questionnaire survey technique. Causes leading to waste in highway projects were identified from the literature as well as from highway construction experts. Subsequently, quantitative data were collected from 127 highway construction professionals using a Likert Scale questionnaire survey, which was ranked using the Relative Importance Index (RII) and further analyzed by using a very robust Factor Analysis (FA) technique. RII results highlight the most significant causes of waste in highway construction, while FA suggests the main factors contributing to the waste in highway projects. The top five most significant causes of waste revealed by this study were: (1) mistakes of surveyors, (2) faulty drawings, (3) incompetence of quantity surveyors, (4) faulty/substandard work, and (5) poor workers' skills, whereas the seven waste factor groups evaluated by the study were: (1) design, (2) storage, (3) survey, (4) workers, (5) waste management, (6) site management, and (7) external. This study further suggested waste management and mitigation strategies for highway construction projects corresponding to each factor group. This is a novel study on waste generation in highway projects in Pakistan and will assist academia and industry practitioners in understanding and controlling construction waste generation in highway projects during various stages of project execution.